The effect The Effect of Dadih Variations as a Probiotic Source in Complementary Food: An In Vivo Study Using White Wistar Rats - Juli Marni; Hasbullah; Rina Yenrina; Kurnia Herlina Dewi; Sri Zulyanti Mardhiah (Universitas Airlangga, 2026)
Enhancing the nutritional quality of complementary foods can be achieved through fortification with probiotic-rich products such dadih. This study aimed to analyze the nutritional composition and evaluate the effects of dadih variations on feed intake, weight gain, feed conversion efficiency (FCE), and protein efficiency ratio (PER). The experiment was conducted using weaned male Sprague-Dawley Wistar rats, aged 21–28 days and weighing ±55 grams. The treatment groups included: A0 (complementary food only), A1 (complementary food + milk), A2 (complementary food + milk + fresh dadih), A3 (complementary food + milk + dadih powder), A4 (complementary food + milk + chocolate dadih powder), and A5 (complementary food + milk + commercial probiotics). A completely randomized design was applied, and data were analyzed using one-way ANOVA at a 5% significance level. Proximate analysis of complementary foods (dry weight basis) demonstrated protein content of 9.67–10.76%, fat 6.26–7.60%, ash 0.63–0.70%, carbohydrate 81.92–83.16%, and energy 418.7–431.46 kcal. Complementary food with dadih (fresh, powdered, and chocolate powdered forms; A2, A3, and A4) significantly improved weight gain, feed intake, FCE, and PER compared with rats receiving complementary food alone (A0), complementary food with milk (A1), or complementary food with commercial probiotics (A5).